Multiple Intelligence of the Fourth Year English Department Students of STKIP Abdi Pendidikan Payakumbuh - Mahaputri, Dwi Settya (Institut Agama Islam Negeri Imam Bonjol Padang, 2014)
Multiple Intelligence (MI) is very important to modern education because its main point is that every individual has eight intelligences and they all work together in a unique way. This research belongs to Descriptive research analyzing students’ MI of the fourth year English department of STKIP Abdi Pendidikan Payakumbuh. The data were collected through questionnaires which had been distributed to 20 students. Then it was analyzed by interpreting in each Intelligence. The finding shows that most of the students had good in Interpersonal Intelligence, Musical Intelligence, and Intrapersonal Intelligence. And they are good enough at Naturalist Intelligence, Bodily-kinesthetic Intelligence, and Spatial Intelligence. However, they are low at Linguistic Intelligence and Logical-mathematic Intelligence.